Unruly Audiences and Dissenting Scholars - Pikli, Natália (Hungarian Journal of English and American Studies, 2022)
Book review:Dunnum, Eric. Unruly Audiences and the Theater of Control in Early Modern London. Abingdon-New York: Routledge, 2020. viii + 264 pages. ISBN 978-0-8153-6933-2. Hb. $140.